ANALISA KEGAGALAN PROGRESIF STRUKTUR PLAT KOMPOSIT CFRP BERLUBANG DENGAN FILLED HOLE PADA PEMBEBANAN TARIK - Yugiantoro, Dwi
The present work aims to obtain progressive failure for filled hole composite plates under tensile loading. For this purpose, a user-defined material model in the finite element analysis package, MSC Patran Nastran, was developed to predict the failure load of the filled hole composite laminates using progressive failure analysis. Tsai-Hill , Hoffman and Maximum stress failure criteria model are studied. In order to achieve the most accurate predictions, the influence of failure criteria and property degradation rules are investigated. Failure modes of the composites model are compared with the same experimental test results from specimen of Indonesian Aerospace. A good agreement between experimental results and numerical predictions was observed. The average maximum load of every configuration is as follow :